10.1016/s1541-9800(05)70729-8 (CrossRef Listing of Deleted DOIs, 2000)
Aim To synthesise qualitative evidence on factors influencing the mental wellbeing of aged care workers across professional roles and system levels. Design Systematic qualitative review. Methods Systematic literature search for qualitative and mixed-methods studies. Data was synthesised using thematic and visual network analyses. Data sources Five academic databases (Medline, Embase, Scopus, PsycINFO, and CINAHL) were searched from 1st January 2014 to 13th March 2025. Results Thirty-eight studies were included, with most focused exclusively on nursing staff (n = 23, 61%). Staff experiences indicated that mental wellbeing challenges in aged care are both widespread and complex. Thematic synthesis identified 13 themes influencing mental wellbeing, including: three micro-level themes (personal factors; work engagement; workers' skills and abilities); seven meso-level themes (job demands; professional relations; job control; leadership; professional development; workplace resources; organisation-level governance); and three macro-level themes (policy and regulation; structure and governance; societal perceptions). Conclusion This review highlights the complex, multi-level factors influencing aged care worker mental wellbeing and underscores the need for coordinated interventions spanning individual, organisation, and broader system-level domains. The review extends existing conceptual models by demonstrating that workforce wellbeing is shaped not only by individual and organisational factors but also by broader societal narratives and governance structures. Implications for practice/policy Improving aged care worker wellbeing is essential for workforce sustainability and quality of care. Findings support the development of targeted, multi-level interventions. Impact Understanding the drivers of mental wellbeing provides aged care providers with a framework for action that goes beyond individual coping, focusing on strengthening workplace environments, including organisational culture, leadership, staffing, and resources. For policymakers, the findings demonstrate how policy and governance decisions shape frontline experiences, offering evidence to guide workforce reform. Reporting method The PRISMA guidelines were used. Protocol registration PROSPERO CRD420251053123. Patient or public contribution No patient or public contribution.